The Role of Knowledge Management, Transformational Leadership, and Organizational Commitment on Employee Performance: Empirical Study in Public Sector - Leviadi Pangaribuan; Aryana Satrya (Jurnal Manajemen Teori dan Terapan)
Objective: This research aims to empirically investigate the influence of knowledge management practices and transformational leadership on employee performance in the public sector, through the role of organizational commitment as a mediator